Evaluation of Cisplatin-Induced Acute Renal Failure Amelioration Using Fondaparinux and Alteplase - Mohamed S. Abdel-Bakky; Anas S. A. Aldakhili; Hussein M. Ali; Ali Y. Babiker; Ahmad H. Alhowail; Salman A. A. Mohammed (MDPI AG, 2023)
Acute renal failure (ARF) is a deleterious condition with increased mortality or healthcare costs or dialysis-dependent end-stage renal disease. The study aims to compare prophylaxis with fondaparinux (Fund) vs. treatment with alteplase (Alt) in ameliorating cisplatin (Cis)-induced ARF. Sixty male mice were equally divided randomly into six groups of control, Cis, Alt, and Cis + Alt groups receiving normal saline for 10 days. All four groups except for the control received Cis (30 mg/kg, i.p.) on day 7, and 6 h later, both the Alt groups received Alt (0.9 mg/kg, i.v.). The animal groups Fund and Fund + Cis received Fund (5 mg/kg, i.p.) for 10 days, and the Fund + Cis group on day 7 received Cis. All the animal groups were euthanized 72 h after the Cis dose. The Fund + Cis group showed significantly increased expression levels of platelet count, retinoid X receptor alpha (RXR-α) and phosphorylated Akt (p-Akt) in addition to decreased levels of urea, blood urea nitrogen (BUN), uric acid, white blood cells (WBCs), red blood cells (RBCs), relative kidney body weight, kidney injury score, glucose, prothrombin (PT), A Disintegrin And Metalloproteinases-10 (ADAM10), extracellular matrix deposition, protease-activated receptor 2 (PAR-2), and fibrinogen expression when compared to the Cis-only group. Meanwhile, the Cis + Alt group showed increased caspase-3 expression in addition to decreased levels of urea, BUN, uric acid, WBCs, RBCs, glucose, platelet count and PT expression with a marked decrease in PAR-2 protein expression compared to the Cis group. The creatinine levels for both the Fund + Cis and Cis + Alt groups were found to be comparable to those of the Cis-only group. The results demonstrate that the coagulation system's activation through the stimulation of PAR-2 and fibrinogen due to Cis-induced ADAM10 protein expression mediated the apoptotic pathway, as indicated by caspase-3 expression through the p-Akt pathway. This is normally accompanied by the loss of RXR-α distal and proximal tubules as lipid droplets. When the animals were pre-treated with the anticoagulant, Fund, the previous deleterious effect was halted while the fibrinolytic agent, Alt, most of the time failed to treat Cis-induced toxicity.